Existentialism Meets Empire: The Theatre of the Absurd and Postcolonial Reflections in Selected African and European Plays - Babatunde Covenant Olugbenga; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
The Theatre of the Absurd emerged as a significant post-World War II movement that profoundly questioned traditional narratives and structures in drama, reflecting the existential philosophy of the era. The movement, largely attributed to the works of Samuel Beckett, Eugene Ionesco, and Jean Genet, explores the absurdity of human existence, characterized by the collapse of conventional meaning in both language and action. Consequently, this work provides a detailed analysis of the origins of the Theatre of the Absurd and postcolonialism. Its philosophical influences, particularly theatre of the absurd from existentialist thought as articulated by Jean-Paul Sartre and Albert Camus, and its impact on contemporary theatre. Postcolonialism is also an essential field of academic inquiry that delves into the multifaceted ramifications of colonialism and imperialism on cultural, political, and economic landscapes. It scrutinizes the enduring effects of human dominion and exploitation over colonized populations and territories. Emerging as a pivotal intellectual framework, postcolonial theory endeavors to unravel the intricate layers of colonial governance and its aftermath, shedding light on the complexities and repercussions therein. By interrogating power dynamics, cultural hegemony, and socio-economic disparities, postcolonialism strives to unveil the enduring legacies of colonial rule, fostering a deeper understanding of historical injustices and contemporary global dynamics. However, this work brings some instances of absurdity in Bode Ojoniyi’s works on A Visit to a Graveyard and Samuel Becket’s Waiting for Goddot. In addition, this work looks into some postcolonial plays by Tunde Fatunde’s No Oil Boom & Sweat and Blood, Wole Soyinka’s Death and the King Horseman and Ahmed Yerima’s The Trials Of Oba Ovonramwen.